Concurrent engineering for composites - Salit, Mohd Sapuan (Universiti Putra Malaysia Press, 2010)
Customers want products that can satisfy their needs and product developers produce products to satisfy those needs while maintaining technical standards at reasonable cost. The balance between these two factors will ensure the success of the product developer and the satisfaction of the users. Concurrent engineering (CE) entails simultaneous consideration of life cycle issues from design brief to disposal, involving all functions within or outside the organization, including engineering designers, sales and marketing personnel, materials engineers, manufacturing engineers and suppliers. In this lecture, concurrent engineering philosophy is applied to composite material. The work involves total design, conceptual design, integration of IT tools, team-work and material selection, using conventional fibre and natural fibre composites. This lecture will begin with a definition of the various terms related to the topic, such as, concurrent engineering, composite materials and product design and development. Selected works on concurrent engineering for composites are reviewed and studies on materials selection systems used in the selection of polymer composites for engineering products are discussed. Further, reviews of conceptual design techniques in the development of composite products are presented. An important issue in composite development, i.e. manufacturing is also studied by looking at two important topics - mould flow analysis and the manufacturing process. Finally a new topic called “design for sustainability” is studied in detail, focussing on the development of ‘green’ products using natural fibre composites